Sleep hygiene games and gamification: where are we and where are we heading? - Liang, Zilu; Melcer, Edward; Hoang, Nhung Huyen; Khotchasing, Kingkarn (Frontiers in Sleep, 2025)
Sleep hygiene encompasses the habits, behaviors, and environmental adjustments conducive to achieving a restful sleep at night. Practices such as maintaining a consistent bedtime routine, avoiding sleep-disruptive substances such as alcohol and caffeine, and ensuring a dark and quiet bedroom are examples of good sleep hygiene. There is growing evidence that well-designed serious games can facilitate desired healthy behavioral changes, suggesting their potential for sleep hygiene intervention. This paper presents a narrative review of existing serious games and gamified systems designed for sleep hygiene intervention in daily life, providing an overview of the current landscape of Sleep Hygiene Games and Gamified Systems (SHG2S). We searched for peer-reviewed publications using four databases including Web of Science, PubMed, ACM Digital Library, and IEEE Xplore. The analysis focused on the targeted sleep hygiene, game design elements, and system evaluation and validation. We found that Accomplishment (e.g., rewards, level-up, leaderboard), Avoidance (e.g., punishment), and Social Relatedness (e.g., group quest, social prod, friending) were the most frequently employed game designs in SHG2S. Most SHG2S focused on addressing nighttime routine, while optimizing sleep environment has largely been underexplored. Existing SHG2S are also limited in addressing different cultural background and sleep patterns. Overall, empirical evidence is still limited regarding whether, why and how gamification leads to favorable effects on sleep hygiene over various temporal scales. Future work should focus on establishing a comprehensive and standardized evaluation framework to facilitate cross-study comparison and to collect evidence on the effectiveness of SHG2S.